Magnetosphere‐ionosphere coupling of global Pi2 pulsations. Issue 4 (16th April 2014) - Keiling, A.; Marghitu, O.; Vogt, J.; Amm, O.; Bunescu, C.; Constantinescu, V.; Frey, H.; Hamrin, M.; Karlsson, T.; Nakamura, R.; Nilsson, H.; Semeter, J.; et al.
Abstract Global Pi2 pulsations have mainly been associated with either low/middle latitudes or middle/high latitudes and, as a result, have been treated as two different types of Pi2 pulsations, either the plasmaspheric cavity resonance or the transient response of the substorm current wedge, respectively. However, in some reports, global Pi2 pulsations have a single period spanning low/middle/high latitudes. This "super" global type has not yet been satisfactorily explained. In particular, it has been a major challenge to identify the coupling between the source region and the ground. Here we report two consecutive super global Pi2 events which were observed over a wide latitudinal and longitudinal range. Using four spacecraft that were azimuthally spread out in the nightside and one spacecraft in the tail lobe, it was possible to follow the Pi2 signal along various paths with time delays from the magnetotail to the ground. Furthermore, it was found that the global pulsations were a combination of various modes including the transient Alfvén and fast modes, field line resonance, and possibly a forced cavity‐type resonance. As for the source of the Pi2 periodicity, oscillatory plasma flow inside the plasma sheet during flow braking (e.g., interchange oscillations) is a likely candidate. Such flow modulations, resembling the ground Pi2 pulsations, were recorded for both events.